2020
DOI: 10.1007/s10903-020-01005-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Immigration-Related Health Concerns in a Federally Qualified Health Center Serving a Diverse Latinx Community: A Mixed Methods Study

Abstract: Background: Immigration-related concerns can impact health and are an important consideration while caring for a multinational Latinx immigrant community.Methods: Patients and caregivers waiting for a non-urgent clinic appointment were randomly screened with one of two social risk screening tools. One tool included a question about "any health or stability concerns related to immigration status." The other tool did not include an immigration health question. Immediately following, respondents were invited to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 39 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…We also found that having more social risks was associated with worse self-reported health, chronic disease and mental health symptoms. Our findings align with other work in immigrant and marginalized communities demonstrating high prevalence of social risk factors and unmet needs, the relationship between social risks and health, and the influence of sociocultural, economic, and political contextual factors in immigrant communities [ 3 , 5 , 6 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also found that having more social risks was associated with worse self-reported health, chronic disease and mental health symptoms. Our findings align with other work in immigrant and marginalized communities demonstrating high prevalence of social risk factors and unmet needs, the relationship between social risks and health, and the influence of sociocultural, economic, and political contextual factors in immigrant communities [ 3 , 5 , 6 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…More and more health care delivery settings and social service agencies are investing in social risk screening and linking to resources [ 2 ]. Multiple studies have identified social risk factors in various sub-populations to inform resource mobilization and tailored screening and referral models [ 3 6 ]. However, little work has been done to examine social risk factors in communities of Middle Eastern and North African (MENA) descent in the U.S., a population known to experience health inequities [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health related social needs (HRSN), including transportation, food insecurity, housing stability and interpersonal violence which are more downstream factors that impact health care, also result directly in both poorer outcomes and weaker health system performance (17,(21)(22)(23). Thus, efforts to systematically collect information on HRSN in clinical settings and develop solutions to address HRSN are on the rise (12,13,16,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Few clinicbased HRSN studies to date, however, have focused on measuring HRSN in languages other than English or Spanish or in diverse immigrant populations, including Asian Americans (AA), where cultural factors and immigration experiences can pose additional barriers to accessing care and routine preventive services (33).…”
Section: Introductionmentioning
confidence: 99%
“…Patients not only approved of immigration-specific screening, but also that including it improved their healthcare experience. By naming an issue that was of high priority to them, immigration screening was received as, "recognition and acknowledgement of the patients' lived experience" [1].…”
mentioning
confidence: 99%